Sharing Sovereignty: State and Non-State Actors in Sub-Saharan Africa Supporting France’s Perception as A Great Power - Balázs, Tamás (Afrika Tanulmányok / Hungarian Journal of African Studies, 2019)
The paper argues that conventional sovereignty can no longer account for France’s perception as a great power, therefore, suggests Stephen Krasner’s approach in analyzing French Africa policy. The basic assumption is that France can maintain its relative power by intervening in weak and failing states in sub-Saharan Africa. Interventions in its former colonies have long played a vital role in enhancing France’s perception as a great power in the international system and in the protection of its vital national interests worldwide. Since the decolonization, there have been around fifty interventions on the continent.